Socio-Demographic Characteristics of Malocclusion among School Children in Dhaka City, Bangladesh (Journal of Monno Medical College, 2023)
Background: Good dental appearance is an increased concern during adolescence and as because malocclusion comprises the health of oral tissues, it can lead to bad dental appearance with social and psychological problems.Objective: The purpose of the present study was to find out the clinico-demographic status of malocclusion among school children.Methodology: This was a cross-sectional study carried out in four high schools at Dhaka city, Bangladesh. The study was conducted from May, 2015 to November, 2015 for a period of 6 (six) months on 384 secondary school children aged between 11 to 16 years by systematic random sampling. The participants were included among those who had no preventive and interceptive orthodontic treatment previously and participants having late mixed or early permanent dentition. Data were collected using a data collection sheet after taking informed consent. The relevant socio-demographic data of the patients were also collected and recorded.Results: The frequency of malocclusion was more common in males (218, 60.1%). The participants were mostly from the middle-class families with monthly incomes of BDT 15,000 to 20,000/month.Conclusion: Malocclusion is found in young age with the middle-class socioeconomic condition.J Monno Med Coll June 2022;8(2): 40-43